Increasing dietary protein acutely augments intestinal iron transporter expression and significantly increases iron absorption in rats. Issue 6 (27th February 2013) - Thomas, Carrie E.; Gaffney‐Stomberg, Erin; Sun, Ben‐Hua; O'Brien, Kimberly O.; Kerstetter, Jane E.; Insogna, Karl L.
Abstract : Iron (Fe) deficiency is endemic worldwide. Little data are available regarding acute effects of dietary protein on intestinal Fe absorption. The current study evaluated the short‐term effects of increasing dietary protein on Fe absorption and expression of genes involved in Fe homeostasis. Sprague Dawley rats (24, female) were randomly assigned to custom‐formulated isocaloric diets containing 40, 20 (control), or 5% protein (as percentage of total kilocalories) for 7 d. Whole‐body Fe balance studies demonstrated that Fe retention was greater in the 40% group than in the 5% group (30.8 vs. 7.3%; P <0.01). In a separate study utilizing stable iron isotopes, the 40% group absorbed 30% of ingested Fe, while the 20% group absorbed 18% ( P =0.005). Whole‐genome profiling revealed that increasing dietary protein from 5 to 40% increased duodenal transcript expression of divalent metal transporter 1 (DMT1) 3.2‐fold, duodenal cytochrome b (Dcytb) 1.8‐fold, and transferrin receptor (TfR) 1.8‐fold. Consistent with these findings, DMT1 transcript expression was 4‐fold higher in RNA prepared from duodenal mucosa in the 40% group compared to the 20% group ( P <0.001). These data suggest that increasing dietary protein increases intestinal Fe absorption in part by up‐regulating DMT1, Dcytb, and TfR.—Thomas, C. E., Gaffney‐Stomberg, E., Sun, B.‐H., O'Brien, K. O., Kerstetter, J. E., Insogna, K. L. Increasing dietary protein acutely augments intestinal iron transporter expression and significantly increases iron absorption in rats. FASEB J. 27, 2476–2483 (2013). www.fasebj.org